“Urban by nature”: The Sokoto jihadist approach to urban planning - Stephanie Zehnle (Afriques)
Like other Islamic reform and state-building movements across the pre-colonial Sahel, the Sokoto Jihad of 1804 had started genuine urbanization processes with architectural references to Islamic ideals of inhabited space. But in the early Sokoto Empire, jihadist urban planning met with a Hausa environment already divided into urban centers and rural areas. Existing Hausa towns were often restructured and enlarged, with a shift from the central position of the palaces towards that of the new mosques built under the aegis of the Jihadist leaders. This article hence analyses the construction of Sokoto as a capital city from the “drawing board” as a case study. In addition, it discusses the location and style of Jihadist mosques in Sokoto, Kano and Zaria within a new concept of Muslim urbanity. Although urban planning in Sokoto was not carried out by map sketches, several maps produced in the Sokoto Empire will be used to study the graphical understanding of Sokoto Jihadist urbanity expressed by rectangular walls and a special mosque-palace order with only very simple and puritan décor. But despite the private activities in mosque building among the male Jihadist elite, Sokoto lacked a state-owned and constant central mosque, because donors and their offspring personally had to care for the upkeep of the buildings. And with the second Sokoto Sultan, Muhammad Bello, urbanization activities gradually shifted from the “old” centers to the frontier of the Empire: on the one hand, militarized border towns (Arabic ribāt, pl. arbita) were erected as profane material protection against military enemies in the periphery. Yet on the other hand, they served as a reference in the Jihadist ideology contrasting the Land of Islam with the Land of Unbelief. The ribāt was a planned city attracting mainly slaves longing for freedom and salvation by the Jihadist promise that any inhabitant of the frontier city would eventually be liberated and enter Paradise. But only for a limited time span did they serve as social and ethnic melting pots on the frontier, before many of them were turned into slave plantations. This phase of intense foundation of fortified settlements must also be understood as a process of sedentarization and aging of the first Jihad soldiers. Equipped with land, wives and slaves from the booty, many soldiers and commanders were settled in new towns and established a living there with their families. The article will thus finally analyze the Sokoto utopia of a completely sedentarized and urbanized Muslim state—a policy propagated both against fellow Fulbe pastoralists and mobile Tuareg allies. This study engages with Sokoto Jihadist urbanization in their theories and practices in the first half of the 19th century and unfolds the Jihadist claims to be “urban by nature.”